Perancangan Aplikasi Arsip Elektronik Fakultas Ilmu Komputer Universitas Prabumulih - Yuntari Purbasari; Suhartini Suhartini; Essy Malays Sari Sakti (Fakultas Teknik Universitas Persada Indonesia YAI, 2023)
Poor management of records in an institution or office will have a negative impact on the performance of the institution or office. The speed and accuracy of obtaining information contained in the archives will affect the quality of leadership decision making. The filing problem faced by institutions or offices is the difficulty of finding the required documents again, this is due to the large number of documents produced from every activity carried out by institutions or offices. This underlies the need for a good filing system management. The design of Electronic Archives carried out by the authors uses the Prototype Model, namely with three stages, including listening to customers, making designs, and conducting trials. This design also uses use case diagrams and activity diagrams to make it easier to define the design between the user and the system. The expected results are in accordance with the original purpose, namely the existence of a computerized system that will minimize the forms of errors and mistakes that usually occur in the old or previous methods.